Manometric evaluation of the motilin receptor agonist camicinal (GSK962040) in humans. Issue 1 (6th August 2017) - Deloose, E.; Depoortere, I.; de Hoon, J.; Van Hecken, A.; Dewit, O. E.; Vasist Johnson, L. S.; Barton, M. E.; Dukes, G. E.; Tack, J.
Abstract: Background: The gut hormone motilin stimulates gastrointestinal motility by inducing gastric phase III of the migrating motor complex (MMC) and enhancing the rate of gastric emptying. Camicinal (GSK962040), a small molecule motilin receptor agonist, has been shown to increase gastrointestinal motility. Methods: In this proof of concept study the effects of camicinal on MMC activity, esophageal and gastric pH was evaluated in eight healthy volunteers as a secondary endpoint. Doses of 50 and 150 mg were compared to placebo for a period of 24 hours in a double‐blinded randomized crossover trial. Key Results: The 50 mg dose (n=4) of camicinal had no significant impact on gastroduodenal manometry or pH parameters. A single dose of 150 mg (n=4) induced a gastric phase III after 0:34 h (0:25‐0:58), which was significantly faster compared to placebo (18:15 h (4:32‐22:16); P =.03). Moreover, the high dose significantly increased the occurrence of gastric phase III contractions compared to placebo (12% vs 39%; P =.0003). This increase in gastric phase III contractions during a period of 24 hour was due to an increased occurrence of gastric phases III during the daytime (5% vs 50%; P =.0001). The same dose however did not affect small bowel manometry parameters or esophageal and gastric pH. Conclusions and Inferences: Considering its stimulating effect on the MMC and gastric emptying, camicinal is an attractive candidate for the treatment of gastroparesis and gastroesophageal reflux disease. This trial was registered at clinicaltrials.gov as NCT00562848. Abstract : A high dose (150 mg) of the motilin receptor agonist, camicinal, induces premature gastric phase III contractions in healthy volunteers.